Acute effect of exercise on kicking accuracy in elite Australian football players - Young, W.; Gulli, R.; Rath, D.; Russell, A.; O'Brien, B.; Harvey, J. (Journal of Science and Medicine in Sport, 2010)
Kicking accuracy (KA) is an important skill in Australian football but the potential influence of exercise on this skill has not been previously investigated. The purpose of this study was to determine if a 2×2min time trial running protocol influenced short KA in elite Australian football. Another aim was to identify if endurance, playing experience and position were related to any exercise-induced KA changes. Twenty-seven professional footballers performed a KA test by kicking at a bullseye on a target projected onto a screen. The mean error from the centre of the target was the KA score. The players were assessed on the KA test, and then performed a 2×2min time trial with a 3-min recovery between runs. The total distance covered was used as a measure of endurance fitness, and the test also served as an exercise bout designed to impose some physiological stress. Immediately following this test, the players walked into the laboratory and performed the KA test again. A paired t-test revealed that the whole group achieved a non-significant 2.7% improvement in KA. Players were divided into two distinct groups based on endurance (2×2min results), playing experience and position (midfielders and forwards/backs). Analysis of covariance showed that after the exercise bout, the fitter group had significantly better KA (p=0.010) than the less fit group, and the more experienced players were 16% more accurate than the less experienced group (p=0.055). The midfielders were 8.2% better than the forwards/backs in KA (p=0.32). It was suggested that greater endurance and playing experience may facilitate KA under moderate physiological stress.